The impact of housing price toward household debt : A case of OECD countries / Mohamad Sulaiman Junaidi - Junaidi, Mohamad Sulaiman (2018)
This study examine the impact of housing price toward household debt in 20 selected OECD countries using panel data within 15 years from 2000 to 2014. The housing price variables that used in this study are House Price Index (HPI), Household Saving (HHS), House Price (HP) and Household Disposable Income (HHDI). The findings showed that all the variables are significant to Household Debt (HHD) except for House Price (HP).